2010
DOI: 10.1038/ng.629
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase initiates activation of epidermal pro-kallikrein and disease onset in a mouse model of Netherton syndrome

Abstract: Deficiency in the serine protease inhibitor LEKTI is the etiological origin of Netherton syndrome. The principal morbidities of the disease are stratum corneum detachment and chronic inflammation. We show that the membrane protease, matriptase, initiates Netherton syndrome in a LEKTI-deficient mouse model by premature activation of a pro-kallikrein-related cascade. Auto-activation of pro-inflammatory and stratum corneum detachment-associated pro-kallikrein-related peptidases was either low or undetectable, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 48 publications
3
100
0
1
Order By: Relevance
“…Loss of LEKTI leaves the activity of several proteases unopposed (Descargues et al, 2005;Deraison et al, 2007), many of which are capable of degrading desmosomes or filag grin, and stimulating inflammation. Protease activation cas cades present an additional layer of complexity by providing an avenue for proteases not targeted by LEKTI to be involved in NS, such as matriptase (Sales et al, 2010) and elastase 2 (ELA2; Bonnart et al, 2010). These unknowns conceal the identity of the most promising pharmaceutical targets in NS and represent a major obstacle in developing targeted thera pies for NS and related skin disorders.…”
Section: Klk5 Is Overexpressed In the Gr Of Tg-klk5 Micementioning
confidence: 99%
See 1 more Smart Citation
“…Loss of LEKTI leaves the activity of several proteases unopposed (Descargues et al, 2005;Deraison et al, 2007), many of which are capable of degrading desmosomes or filag grin, and stimulating inflammation. Protease activation cas cades present an additional layer of complexity by providing an avenue for proteases not targeted by LEKTI to be involved in NS, such as matriptase (Sales et al, 2010) and elastase 2 (ELA2; Bonnart et al, 2010). These unknowns conceal the identity of the most promising pharmaceutical targets in NS and represent a major obstacle in developing targeted thera pies for NS and related skin disorders.…”
Section: Klk5 Is Overexpressed In the Gr Of Tg-klk5 Micementioning
confidence: 99%
“…As our construct expresses KLK5 as a proprotease, this implies that it has been activated in vivo. It has recently been shown that matriptase can activate pro KLK5 and pro KLK7 in vitro (Sales et al, 2010). KLK5 has been shown to activate pro KLK7, pro KLK14, and pro ELA2, as well as to amplify cas cade initiation by activating pro KLK5 in vitro (Brattsand et al, 2005;Bonnart et al, 2010).…”
Section: Klk5 Hyperactivity Leads To Cutaneous Signs Of Allergy and Imentioning
confidence: 99%
“…Matriptase initiates disease onset in a mouse model of NS by activating epidermal KLKs (Fig. 4) [41]. Ablation of matriptase from NS-model mice prevented detachment of stratum corneum and improved the 11 barrier function of the epidermis.…”
Section: Lekti and Netherton Syndromementioning
confidence: 99%
“…This process, desquamation, is accomplished via degradation of corneodesmosomes by a proteolytic cascade of human kallikrein-related peptidases (KLKs) (14). It is thought that the cascade is initiated by activation of trypsin-like pro-KLK5, either by autoactivation or by matriptase in Netherton syndrome (15). Subsequently KLK5 activates other trypsin-like KLKs and chymotrypsin-like KLK7 by proteolytic release of the amino-terminal propeptide.…”
mentioning
confidence: 99%